Interorganizational learning: a strategic framework for service networks. Issue 2 (10th August 2020) - Peronard, Jean-Paul
Abstract : Purpose: The purpose of this paper is to understand the link between the organizing of service networks and interorganizational learning strategies. Design/methodology/approach: By deepening the conceptual understanding of service networks and their central properties, an overview of the learning challenges for improved performance is provided. The implications of learning are then discussed using four conceptual types to advance our understanding of learning in various service networks. Two different frameworks are combined, one designed to analyze the properties of service delivery and the other to understand their interorganizational learning implications for different types of service networks. Findings: This paper examines the central properties of service network delivery and explains their implications for interorganizational learning strategy operationalized in a service network typology. Practical implications: The proposed framework deepens the understanding of the concept of service networks and brings attention to properties that have implication for interorganizational learning. Knowing the central properties in detail and their major organizing challenges allows for learning strategies to improve service network performance. Originality/value: The value lies in the deepening the understanding of interorganizational learning in service networks, which is much needed in the growing body of literature on both concepts.